Communicating culture through language (examples of russian adjectival phraseology) - Nazmieva, Elmira Ildarovna; Andreeva, Elena Anatolyevna; Sakhibullina, Kadria Azatovna (Universidade Estadual Paulista, 2021)
In this paper, phraseological units are considered as the most valuable source of information about the culture and mentality of a people of a certain nation; they are often preserved in folklore, customs and traditions, and can be found in literature. In order to recognize a lexical unit as a concept, a keyword of culture is necessary, so it is commonly used, frequently included in phraseological units or proverbs, sayings, and so on. In this study, several phraseological units that reflect traditions and customs of English, Australian and Russian people are discussed. The main focus of the study was on adjectival phraseological units, which are those correlated with adjectives, with the purpose of revealing their meanings, based on various cultural and historical factors. Meanings can be communicated from a variety of positions and even different approaches from which a culture is considered. Phraseological Units enrich each language and are inextricably linked with the culture of the native speakers. More than 900 units of various structures in Russian were found, and then located in sentences from the Russian language corpus. For emphasizing the connection of the units with the culture in which they were formed, examples representing Russian cuisine, stereotypes, climate and others were selected for the article.